The Effect of Duration of Amidation of Fatty Acids with Diethanolamine on the Surfactant Properties; Journal of Surfactants and Detergents; Vol. 22, iss. 3 - Yanovsky V. A.; Andropov M. O.; Fakhrislamova R. S.; Churkin R. A.; Minaev K. M. Konstantin Madestovich; Yanovskaya E. A. (2019, 2019)
Title screen